Assessment of peripheral nerve affection of the lower limbs in type 2 diabetic patients using neuromuscular ultrasound and electrodiagnostic studies - Mary Fayez Francis Hana; Mona Mansour Hasab El Naby; Ola Abdulnaser Abdulaziez Saied; Youssy Saeed Eshak Gergius (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Diabetic peripheral neuropathy is regarded as one of the most common microvascular sequalae of type 2 diabetes mellitus which leads to lower limb complications. Lately, the focus has shifted to early detection of diabetic neuropathy in the subclinical stage. While nerve conduction studies are considered non-invasive, sensitive and objective procedures for diagnosis of neuropathies, the missed diagnosis rate is high in early neuropathy. Recently, ultrasonography use has been regarded as an alternative method for detecting neuropathies, being an inexpensive and a more comfortable tool. The aim of this study was to define the pattern of affection of lower limb peripheral nerves in type 2 diabetic patients using neuromuscular ultrasound and to assess its utility in evaluation of diabetic peripheral neuropathy in asymptomatic diabetic patients. Methods This cross-sectional study included 40 type 2 diabetic patients and 20 healthy age- and sex-matched controls. All patients were subjected to full history taking, clinical examination, electrodiagnostic studies and neuromuscular ultrasound. Neuromuscular ultrasound was performed for tibial, fibular and sural nerves bilaterally for all patients and controls. Nerve cross-sectional area was measured at multiple sites for each nerve. Results Diabetic patients had statistically significant higher mean cross-sectional area values than controls in nearly all examined sites of all nerves. Furthermore, patients with electrophysiological diabetic peripheral neuropathy (EDPN) had higher statistically significant mean sural cross-sectional area values than patients without EDPN. There were no statistically significant differences in mean cross-sectional area values between symptomatic and asymptomatic patients with EDPN in all measured nerves. ROC analysis showed that sural nerve cross-sectional area cut off value of > 5 mm 2 was predictive for diagnosis of EDPN. Conclusions Diabetic cases, even asymptomatic ones, had statistically significant higher mean cross-sectional area values than controls on neuromuscular ultrasound. In addition, patients with EDPN showed higher cross-sectional area values of lower limbs peripheral nerves. Thus, neuromuscular ultrasound could be used as a screening tool for diabetic peripheral neuropathy using sural nerve cross-sectional area measurement at the ankle even in asymptomatic diabetic patients.